The role of collaboration in innovation at cultural and creative organisations. The case of the museum. (4th May 2019) - Li, Chuan; Ghirardi, Sendy
ABSTRACT: Museums are art and cultural organisations that can be powerful levers for local development from a socio-economic viewpoint. Innovation is a key to enabling them to accomplish this task. Emphasis has been placed on the relationship between collaboration and innovation in the existing literature, which focuses mostly on case studies of technological innovation in large cultural organisations. Conversely, this study concentrates on impacts of different collaborative arrangements on technological and cultural innovation in small and medium-sized cultural organisations, specifically museums. Based on a survey on museums in the Valencia region, Spain, the ANOVA method was used to determine if there were differences in innovation outcomes between museums that did, or did not, collaborate with specific actors. The results reveal the collaboration with universities and high-tech firms and inter-museum collaboration can enhance technological innovation while joining professional associations can improve cultural innovation. Based on these results, some policy implications are developed.